Digital Synergy: Examining How IoT, Blockchain and AI Collectively Improve Supply Chain Transparency - Karthiga, S. Jenitha; Muthukumaran, Kavitha; Jhansi, V.; Jayasingh, Sudarsan; Rashma, M. Micheal; Lekshmi, R. S. (International Review of Management and Marketing, 2026)
This research is aimed at investigating the role of new technologies in supply chain transparency and traceability. In particular, the study focuses on the ways the emergent technologies, such as the Internet of Things (IoT), Blockchain (BC), and Artificial Intelligence (AI) transform the visibility and accountability within the network of supply chains. Data were collected by a survey-based approach where the respondents were professionals working in different fields of the supply chain and the data were analyzed using Structural Equation Modelling to determine the technological pathways that play a significant role in enhancing transparency, traceability, and accountability. The results indicate that IoT can be used to take data in real-time and monitor it continuously, BC can be used to ensure that data are stored in a secure and tamper-proof manner, and AI can be used to enhance predictive analytics and automated decision-making. All these technologies provide better data integrity, access, and accuracy and minimize the risk of manual tracking and disjointed information systems. They also help to detect disruption faster and enhance coordination between stakeholders, which contributes to the higher adherence of regulatory and quality standards. In general, the paper has shown that the combined application of the IoT, BC, and AI can bring certain benefits to the supply chain in terms of transparency and resilience significantly, which supports their role in contemporary supply chain remodeling.